Catheterized Fiber-Optics Confocal Microscopy of the Beating Heart In Situ. (October 2017) - Huang, Chao; Wasmund, Stephen; Hitchcock, Robert; Marrouche, Nassir F.; Sachse, Frank B.
Abstract : Supplemental Digital Content is available in the text.